Application of The Think Pair and Share on Writing Skills of Story Text in Class X SMA Students - Nasrul Bagus Fajriansyah Nasrul; Euis Eti Rohaeti (IKIP Siliwangi, 2023)
This study was conducted to determine the application of the think, pair, and share models to the skills of writing saga texts. The method used when researching experimental methods is to determine the application of the think pair and share learning model in the experimental class with the ordinary learning model in the control class. Collecting data using pre-test and post-test in the control and experimental classes. The data were analyzed using the SPSS 24 application by looking at the scores obtained by the students, the normality test to determine whether the class was usually distributed, and finally, the t-test to determine the application of the think, pair, and share model to determine the students' scores. The mean score of the control class in the initial test was 77.53 and the final test was 79.97. The result of the average value of the experimental class in the initial test was 79.94 and in the final test. get 82.28. Based on the results of the normality test obtained 0.200 data indicates that the distribution is normal. The t-test obtained data 0.000 <0.05, meaning that H0 was rejected and Haa accepted, so implementing the think, pair, and share model on the skills of writing saga texts was affected.